Advances in the study of the role of high-frequency mutant subunits of the SWI/SNF complex in tumors - Zhao, Jiumei; Zhu, Jing; Tang, Yu; Zheng, Kepu; Li, Ziwei (Frontiers in Oncology, 2024)
SWI/SNF (Switch/Sucrose non-fermentable, switch/sucrose non-fermentable) chromatin remodeling complex is a macromolecular complex composed of multiple subunits. It can use the energy generated by the hydrolysis of ATP (Adenosine triphosphate) to destroy the connection between DNA and histones, achieve the breakdown of nucleosomes, and regulate gene expression. SWI/SNF complex is essential for cell proliferation and differentiation, and the abnormal function of its subunits is closely related to tumorigenesis. Among them, ARID1A, an essential non-catalytic subunit of the SWI/SNF complex, can regulate the targeting of the complex through DNA or protein interactions. Moreover, the abnormal function of ARID1A significantly reduces the targeting of SWI/SNF complex to genes and participates in critical intracellular activities such as gene transcription and DNA synthesis. As a catalytic subunit of the SWI/SNF complex, SMARCA4 has ATPase activity that catalyzes the hydrolysis of ATP to produce energy and power the chromatin remodeling complex, which is critical to the function of the SWI/SNF complex. The study data indicate that approximately 25% of cancers have one or more SWI/SNF subunit genetic abnormalities, and at least nine different SWI/SNF subunits have been identified as having repeated mutations multiple times in various cancers, suggesting that mutations affecting SWI/SNF subunits may introduce vulnerabilities to these cancers. Here, we review the mechanism of action of ARID1A and SMARCA4, the two subunits with the highest mutation frequency in the SWI/SNF complex, and the research progress of their targeted therapy in tumors to provide a new direction for precise targeted therapy of clinical tumors.